Concussion and National Hockey League player performance: An advanced hockey metrics analysis - Buckley, T. A.; Bryk, K. N.; Van Pelt, K. L.; Broglio, S. P.; East, S. A.; Zuckerman, S. L.; Kuhn, A. W. (Journal of Athletic Training, 2019)
Context Postconcussion deficits in neurocognitive performance and postural control may persist at the time of return to sport participation. How these deficits, if present, affect athletic performance is largely unknown, with prior studies showing mixed results.